2022
DOI: 10.1177/19485506221119018
|View full text |Cite
|
Sign up to set email alerts
|

Collective Stressors Affect the Psychosocial Development of Young Adults

Abstract: Young adulthood is a critical developmental life stage and a period of enhanced vulnerability to stress. In 2020, young adults in Northern California were faced with a series of unforeseen, collective stressors: the COVID-19 pandemic, extreme wildfires, social tension associated with the murder of George Floyd, and a contentious election that culminated in an attack on the nation’s capital. In a natural experiment, we compared the psychosocial development of 415 young adults across 8 monthly assessment waves d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…However, it is important to keep in mind that these data were collected during the COVID-19 pandemic. Although evidence is mixed regarding the effects of COVID-19 on personality change ( Bühler et al, 2021 ), it seems plausible that people perceived themselves as less agreeable and open during the pandemic, which is the pattern we observed. Moreover, we did not specify how far in the past the respondent should consider (e.g., 1 month, 1 year, 5 years), and it is possible that findings were affected by variation in which past self respondents had in mind.…”
Section: Discussionsupporting
confidence: 59%
“…However, it is important to keep in mind that these data were collected during the COVID-19 pandemic. Although evidence is mixed regarding the effects of COVID-19 on personality change ( Bühler et al, 2021 ), it seems plausible that people perceived themselves as less agreeable and open during the pandemic, which is the pattern we observed. Moreover, we did not specify how far in the past the respondent should consider (e.g., 1 month, 1 year, 5 years), and it is possible that findings were affected by variation in which past self respondents had in mind.…”
Section: Discussionsupporting
confidence: 59%
“…Multiple studies found that mental health impacts from the COVID-19 pandemic and wildfires disproportionately impacted individuals of non-male gender, younger age, and with pre-existing mental health conditions. These findings are reinforced by Bühler et al's evidence that the COVID-19 pandemic, wildfires, and other contemporary sociopolitical tensions inflicted cumulative mental health stressors that harmed young adults' psychosocial development [54]. Remarkably, no risk factors or vulnerable groups were identified in the impact of wildfire on COVID-19 infection outcomes within the existing evidence base, primarily because such risk factors were not considered in the study designs.…”
Section: Discussionmentioning
confidence: 99%
“…While the impacts of the pandemic are still being investigated, some studies have noted significant changes in variables relevant to our study such as life satisfaction (Ammar et al., 2020; Bono et al., 2020), perceived stress (Bono et al., 2020), and positive and negative affect (Lades et al., 2020). Moreover, a number of other significant stressors that occurred during the summer of 2020, including the murder of George Floyd and destructive wildfires on the West Coast of the United States, may have introduced complexity to patterns of change and reduced our ability to isolate the effects of studying abroad (Bühler et al., 2021).…”
Section: Discussionmentioning
confidence: 99%